The Intricate Chemistry of Cobalt(II) Halides and Bis(diphenylphosphanyl)ethane. Issue 28 (1st August 2013) - Kiefer, Gregor; Vrubel, Heron; Scopelliti, Rosario; Severin, Kay
Abstract: Phosphane complexes of the putative formula [CoX2 (dppe)] [X = Cl, Br, I; dppe = bis(diphenylphosphanyl)ethane] are frequently used catalyst precursors in cobalt‐catalyzed reactions. Despite their widespread use, these complexes have not been structurally characterized. We demonstrate that synthetic procedures for [CoX2 (dppe)] afford complexes of the formula [Co4 X8 (dppe)5 ] instead. Crystallographic analyses of these complexes reveal an ionic structure with pentacoordinate [CoX(dppe)2 ] + cations and a dinuclear [Co2 X6 (dppe)] 2– anion. The bromido and iodido complexes crystallize in two forms, which differ in the geometry of the cation (square‐pyramidal vs trigonal‐bipyramidal). Abstract : Complexes of the putative formula [CoX2 (dppe)] are frequently used as catalyst precursors in cobalt‐catalyzed reactions. Crystallographic analyses show that these complexes are in fact ionic compounds of the formula [Co4 X8 (dppe)5 ].